Science and Technology Reciprocity in Educational Laboratory Systems Intermediate in Kota Sungai Penuh - Sastria, Emayulia (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
The determination of science and technology is a prerequisite for the development of modern laboratory systems. This study examines the laboratory management system in the interrelationship between science and technology. Qualitative evaluation methods are used to accommodate research questions related to the comparison of objectives and realities of laboratory systems. The focus of research lies in the management system and management paradigm of science and technology. The study was conducted in all public high schools in Kota Sungai Penuh, Jambi. The study used naturalistic observation to observe laboratory conditions and semi-structured interviews from laboratory managers, educators involved in the laboratory and students. Research bias is minimized by comparing observations and some interview results. The results showed that there is a gap in laboratory management of schools in newly developing cities. This slice of science and technology in the laboratory management system is influenced by past views, present feelings and future assumptions from laboratory managers, parties and educators involved. Then policy and policy realization magnify the gap created. The gap can be addressed by using virtual labs.